Malawi: Yield Cuts Survey - Lilongwe University of Agriculture and Natural Resources; Agriculture Extension Services; Michigan State University (International Food Policy Research Institute, 2015)
This study contains data from a survey about yield cuts in Malawi. Project title: Malawi: Yield Cuts Survey. Project abstract: The Malawi project has local theme 'Agro-ecological intensification in Malawi through action research with smallholder farmers' with a lot of emphasis on co-learning with farmers and other stakeholders.The purpose of the Africa RISING Malawi component is to enhance farmer knowledge and support sustainable intensification (SI) pathways for productivity gains in maize-legume diversified systems, that also integrates livestock-related enterprises such as improved fodder for intensified dairy production. The project is setting up a research approach that systematically assesses SI best-bet options that appropriately respond to the needs of resource-poor farmers - particularly female headed households. Building on successful examples of participatory action research and experiences from biophysical research on smallholder farms in Malawi over the past 2 decades, the research team has begun taping into these products of agricultural research to move towards more sustainable smallholder production systems. We envisage that farm-scale production strategies employed by different farm/farmer typologies will be further distilled through scenario analyses using farming systems simulation modeling approaches. The project works with an alliance of actors, (agro-dealers, extension services, NGOs, local government structures, etc) as R4D platforms for the two districts. Project website: http://africa-rising.net